2002
DOI: 10.1034/j.1600-0773.2002.910402.x
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis Sampling of Carbamazepine, Phenytoin and Phenobarbital in Subcutaneous Extracellular Fluid and Subdural Cerebrospinal Fluid in Humans: An in vitro and in vivo Study of Adsorption to the Sampling Device

Abstract: The purpose of the study was to determine if binding of the drugs to the sampling equipment during microdialysis would influence the results for carbamazepine, phenytoin and phenobarbital. In vitro experiments with microdialysis catheters and separate parts of catheters were performed to estimate the degree of drug binding to the dialysis equipment. A mathematical model to calculate drug binding and recovery is proposed. In vivo protein unbound carbamazepine concentrations in subcutaneous extracellular fluid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Non-specific binding to the plastic tubing or dialysis membrane has been largely attributed to lipophilicity of the test compound (Lindberger et al, 2002). Additives investigated for reducing non-specific binding include the addition of albumin (Carneheim and Stahle, 1991), beta-cyclodextrin (Khramov and Stenken, 1999a), CHAPS [(3-cholamidopropyl) dimethylammonio-1-propanesulphonate] (Silvester and Zang, 2012) or polysorbate-80 (Loos et al, 2007) in order to saturate the binding sites on the microdialysis tubing and dialysis membrane (Pitt et al, 1988;Traunmuller et al, 2006), thereby reducing the non-specific binding of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Non-specific binding to the plastic tubing or dialysis membrane has been largely attributed to lipophilicity of the test compound (Lindberger et al, 2002). Additives investigated for reducing non-specific binding include the addition of albumin (Carneheim and Stahle, 1991), beta-cyclodextrin (Khramov and Stenken, 1999a), CHAPS [(3-cholamidopropyl) dimethylammonio-1-propanesulphonate] (Silvester and Zang, 2012) or polysorbate-80 (Loos et al, 2007) in order to saturate the binding sites on the microdialysis tubing and dialysis membrane (Pitt et al, 1988;Traunmuller et al, 2006), thereby reducing the non-specific binding of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is known as the relative recovery and is a consequence of the transit time of the perfusate along the semi-permeable microdialysis membrane being insufficient to allow complete equilibration between ECF and perfusate. Relative recovery of phenytoin has been investigated by several authors using a variety of catheter types, membrane lengths and perfusion rates 10,15,16 . However, it has not previously been reported for the commonly used catheter type and perfusion rate we describe in this study.…”
Section: Discussionmentioning
confidence: 99%
“…One challenge to the use of microdialysis is the low probe recovery of lipophilic compounds. The low recovery of these compounds can be attributed to the tendency of these compounds to bind to the sampling components, their poor solubility in hydrophilic perfusates, their high protein binding affinity (which limits the unbound drug in the sampling space), and their tendency to accumulate in the intracellular compartment, which reduces the sampling pool in tumor ECF (Lindberger et al, 2002;Loos et al, 2007;Wang et al, 2008). This challenge is particularly significant because many of the compounds under development for treatment of brain tumors tend to exhibit lipophilic properties.…”
Section: Chapter 5 Summary Discussion and Future Directionsmentioning
confidence: 99%
“…Previous studies have reported irreproducible dialysis of lipophilic drugs (Lindberger et al, 2002;Loos et al, 2007;Wang et al, 2008). In addition, previous studies have only evaluated a single anti-cancer agent, an approach that has limited relevance in light of the prevalent use of combinations of two or more anti-cancer drugs in therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation